A Study to Evaluate the Impact of a Self-instructional Module on Knowledge Enhancement Regarding the Management of Common Pregnancy Discomforts Among Primigravida Mothers in Selected Hospitals of Mysuru - Anusha P.S.; S.R. Raksha (International Journal of Midwifery Nursing And Practices, 2025)
Gestation is a time of physical, emotional and hormonal changes in a woman. It is one of the important phases in a woman’s life from the time of be. It is accompanied by discomforts that are generally known as minor ailments. These common discomforts occur generally among primigravida mothers. Symptoms of discomfort due to gestation vary from woman to woman; they are nausea and vomiting, fatigue, backache, heartburn and indigestion, swollen modes, frequence of urination, constipation, edema of legs, dizziness etc. Understanding these common discomforts and taking acceptable probative and preventative measures is a high responsibility of every pregnant woman in order to avoid the complications. Hence, we planned to conduct the present study that may serve salutary to the primi mothers especially. The study aimed to evaluate the current knowledge of primigravida mothers regarding the management of common discomforts during pregnancy, assess the effectiveness of a self-instructional module (SIM) on improving this knowledge, and examine the relationship between pretest knowledge scores and selected demographic variables. A quantitative evaluative research study with a pre-experimental one-group pre-test post-test design was conducted using convenient sampling (N=60). Data were collected through a structured interview, followed by the administration of the self-instructional module. Descriptive and inferential statistics were used to analyze the data. The results revealed that the mean pre-test score was 15.3, and the mean post-test score was 25.75, with a mean difference of 10.42. The computed paired ‘t’ value of 16.63 was statistically significant at the 5% level, indicating that the self-instructional module was effective. As a result, the research hypothesis (H1) was accepted, showing a significant difference between the mean pre-test and post-test knowledge scores. The calculated chi-square values showed no significant association between the socio-demographic data of the respondents and their pre-test knowledge scores. In conclusion, the study found a knowledge deficit regarding the management of common discomforts during pregnancy among primigravida mothers prior to the administration of the SIM. The results demonstrated that the SIM was effective in increasing knowledge.
Keywords: Knowledge; SIM; common discomforts; effectiveness; management; primigravida mother